Criminal Appeals as Jury Control: An Anglo-Canadian Historical Perspective on the Rise of Criminal Appeals - Berger, Benjamin L. (Canadian Criminal Law Review, 2005)
The appeal plays a central role in the modern Canadian criminal justice system. Appellate rulings are the primary means by which, through the assessment of trial error, substantive criminal law and the law of evidence evolve and develop. Scarcely more than a century ago, however, formal criminal appeals were unknown to Anglo-Canadian criminal procedure. What provoked the creation of a criminal appellate procedure? Why and how did criminal appeals emerge in Canada at the end of the 19th century? Answers to these questions can enrich our appreciation of the essential nature and function of the modern criminal appeal. This article examines the 19th century English debates on the establishment of a criminal appeal and places these debates in the context of the loss of the old forms of jury control in the 18th century. The author shows that the emergence of the criminal appeal was closely tied to a 19th century debate between the judges of England and members of the legal profession about the frailties of trial by jury and the need for a new means of trial error correction. The author argues that, accordingly, the modern criminal appeal is best understood as, at core, a mechanism of jury control. [PUBLICATION ABSTRACT]